PERANAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN PROVINSI RIAU: ANALISIS STRUKTURINPUT-OUTPUT - Meilisa Fajriani; Djaimi Bakce; Jumatri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Indonesia at this time stillincluding developing countriesas well as in Province of Riau, which is part of Indonesia.This is proved by the large majority of the population who worked in the agricultural sector and the largest contributor to non oil and gas GDP. The purpose of this study was to know the role the agricultural sector from the structure of the economy Province of Riau. The data used is the input-output table in 2012 with 20 x 20 sector classification obtained from the Badan Perencanaan Daerah (Bappeda). The analysis method used in this research is descriptive analysis. Analysis the role of agriculture conducted through of reviews from the input side and output side. The results shown that contribution of agricultural sector in province of Riau is big enough, where it is reflected from a large contribution of output compared to other sectors. Components formation of output to show that output side of agricultural sector is driven by further consumption followed investment and exports. While the components of input side is driven by producer surplus followed by wage-salary and depreciation. Based on these results in order to create a conducive economy, it’s necessary to efforts increase direct and indirect investment through capital accumulation that comes from producer surplus. Consumtion this time it is the largest constituent components. Although it Is the largest constituent components, but consumption can't create added value for the economy. If the investment continues to be improved in addition to increasing the value added to the economy, is also expected an increase in producer surplus that will be reused on the next investment activity. Keywords: The role of agricultural sector, input-output table, investment, producer surplus